Designing an Enterprise Architecture for an Electronic Football Match Ticket Sales Information System at Kanjuruhan Stadium Using The Zachman Framework - Jayanto, Jevin; Fathin, Naufal; Pakaja, Fachrudin (oneamd.com, 2025)
This research aims to design an enterprise architecture for an electronic football match ticket sales information system at Kanjuruhan Stadium using the Zachman framework. A qualitative method with a case study approach at Kanjuruhan Stadium was employed. Data collection techniques included in-depth interviews with prospective users (spectators) and stadium management staff, observations of existing processes, and a review of operational documentation. The collected data were thematically analyzed to identify the needs, perceptions, constraints, and expectations of stakeholders. The findings reveal various challenges in the existing manual processes, such as long queues and potential ticket security issues. Qualitative analysis indicates a profound need for a system that is easily accessible, informative, secure, and supported by responsive services, all contributing to an enhanced user experience. Based on this in-depth understanding from the qualitative findings, the design of the information system architecture using the Zachman Framework facilitates a structured mapping of needs and solutions from conceptual to implementational levels. The implications of this research suggest that the Zachman Framework, informed by in-depth qualitative analysis, can be a strategic approach for developing information systems in large-scale institutions, particularly in supporting the digitalization of public services in the sports sector